The Push-Pull Effects of Expressways: The Case of TPLEX for Baguio City, Philippines - Mabazza, Daniel L.; Latonero, Glenn Simon (Journal on Transportation System and Engineering, 2025)
This study investigates the impact of the Tarlac-Pangasinan-La Union Expressway (TPLEX) on the tourism industry of Baguio City, Philippines. By analyzing historical trends in tourist arrivals and expressway development, the study establishes a strong correlation between increased accessibility and heightened visitor influx. Findings indicate that expressway openings reduced travel time and stimulated continuous tourism growth, even beyond traditional peak seasons. These results confirm the role of expressways in overcoming the friction of distance and illustrate their push-pull effects on urban mobility. The study highlights the need for integrated planning to mitigate potential congestion and suggests further research on employment shifts and regional migration patterns.